Platelet to White Blood Cell Ratio (PWR) to Predict Mortality in Acute on Chronic Liver Failure of Cirrhosis Patient: A Systematic Review - Pandapotan, Roy Akur; Gunawan, Burhan (The Indonesian Society for Digestive Endoscopy, 2022)
Background: Liver cirrhosis (LC) is still being important public health concern, due to the rising of global incidence and mortality. There is risk progression in LC patients to acute-on-chronic liver failure (ACLF) patients with high incidence of complication and high short-term mortality rate. It needs rapid and simpler predictor to immediate and accurate triage of the patient. The aim of this study is to review systematically the role of PWR to predict the mortality in ACLF cirrhosis patient.Method: This systematic review study was identified by searching Pub-Med, Cochrane library, and EMBASE database (2016-2022). Only observational studies were included. ACLF patient was selected as the main subject in each study, and PWR was added as short-term mortality predictor. The Cochran seven step model was used to perform the review.Results: Six cohort retrospective studies met inclusion criteria, including total 1,348 patient ACLF. Half of studies included had high level of evidence. The non-survivor ACLF patient had significantly lower PWR values than survivor. The range of HR of PWR to predict mortality in ACLF was 0.665-0.995, with p value 0.0001. Whereas the cutoff range of PWR value to predict non survivor in ACLF patient was 7.83-14.2.Conclusion: PWR had a predictive efficacy, similar to CLIF-SOFA and MELD score in terms of predicting short-term mortality in ACLF patients. PWR showed significantly independent risk factor of short term mortality in ACLF cirrhotic patient.